PEMANFAATAN LIMBAH PLASTIK SEBAGAI ALTERNATIF BAHAN PELAPIS (UPHOLSTERY) PADA PRODUK INTERIOR - Sofiana, Yunida (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Environmental pollution caused by waste, especially plastics is unavoidable nowadays. Recycling is one of the creative methods that can be done to reduce the amount of plastic waste on the rise. Waste plastics can be recycled into a substitute raw material for woven natural materials (pandanus), which is already decreasing and hard to find and can also be used as an alternative coating material or upholstery on interior products. Processing of plastic waste until it is in the ready-to-use stage is easier to do than natural materials since it does not have to go through many stages such as drying and coloring. In addition, plastic waste has a modern color and texture, therefore creativity and foresight in making use of its advantages is needed by designing products that fits. Benefits of using plastic material compared to natural materials are strength, smoother texture, glossy and more resistant to water.